Examining Policy Implementation in Health Care: Rule Abidance and Deviation in Emergency Medical Services - Henderson, Alexander C. (Public administration review, 2013)
Passage of the Patient Protection and Affordable Care Act (ACA) has served to refocus attention on the complexity of health care delivery in the United States, with particular attention to concepts of quality, access, and outcomes. This article argues that our understanding of the ACA must be informed by an examination of policy implementation in health care, including the core public function of emergency medical services (EMS). Key concepts of implementation in frontline service—notably, rule abidance and deviation—are examined from the perspective of street-level EMS workers. Results indicate that the intersection of rules, patient needs, and professional culture creates instances of both rule abidance and deviation, both of which contribute substantively to concepts of quality in a health care setting.